1994
DOI: 10.1099/13500872-140-7-1533
|View full text |Cite
|
Sign up to set email alerts
|

A Candida albicans cyclic nucleotide phosphodiesterase: cloning and expression in Saccharomyces cerevisiae and biochemical characterization of the recombinant enzyme

Abstract: We have cloned a Candida albicans gene, which encodes a cyclic nucleotide phosphodiesterase (PDEase), by complementation in a Saccharomyces cerevisiae PDEase-def icient mutant. The deduced amino acid sequence is similar to that of the low-affinity PDEase of 5. cerevisiae (PDEI) and the cyclic nucleotide PDEase (PD) of Dictyostelium discoideum. Biochemical analysis of recombinant protein produced in 5. cerevisiae indicated that the enzyme behaves as a PDEl homologue: it hydrolyses both cAMP (Km = 0.49 mM) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 49 publications
2
43
0
Order By: Relevance
“…CaPDE2 is functional in S. cerevisiae, but is toxic upon overexpression Previous attempts to clone the C. albicans homologue of PDE2 by functional complementation have been unsuccessful (Hoyer et al, 1994;Taylor, 1999). However, a putative CaPDE2 ORF, with the conserved signature motif of a class I cAMP PDE (HDVGHPGTTNDF) (Charbonneau et al, 1986), 1716 bp long and with 28 % aa identity to ScPDE2, was revealed by the Candida genome sequence project (Tait et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CaPDE2 is functional in S. cerevisiae, but is toxic upon overexpression Previous attempts to clone the C. albicans homologue of PDE2 by functional complementation have been unsuccessful (Hoyer et al, 1994;Taylor, 1999). However, a putative CaPDE2 ORF, with the conserved signature motif of a class I cAMP PDE (HDVGHPGTTNDF) (Charbonneau et al, 1986), 1716 bp long and with 28 % aa identity to ScPDE2, was revealed by the Candida genome sequence project (Tait et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…7). CaPDE1 has been cloned, but no capde1 mutants have yet been constructed (Hoyer et al, 1994). Analysing such mutants might help to elucidate the more specific roles of the low-affinity cAMP PDE in C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is one additional phosphodiesterase in Candida, the low-affinity cAMP phosphodiesterase, encoded by PDE1 (Hoyer et al, 1994). At present there are no mutants available and the phenotypic consequences of its deletion are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Two phosphodiesterase-encoding genes PDE1 and PDE2 have been found in the fungal pathogen C. albicans (Bahn et al, 2003;Hoyer et al, 1994;Jung and Stateva, 2003). Mutants lacking PDE1 are not yet available; however, hetero-and homozygous pde2 null mutants have been generated and characterized (Bahn et al, 2003;Jung and Stateva, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As a group they have been designated as class I PDEs. Additional forms of PDEs have been described in Saccharomyces cerevisiae (8), Dictyostelium discoideum (9), Vibrio fisheri (10), and Candida albicans (11), which exhibit very little amino acid sequence identity to the class I enzymes. These enzymes, currently designated as class II PDEs, likely have a different evolutionary origin because, in contrast to all other eukaryotic PDEs, they have catalytic domains unlike those in mammalian class I enzymes (8).…”
mentioning
confidence: 99%